1990
DOI: 10.1177/002221949002300205
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing in Dyslexia

Abstract: The temporal processing capabilities of 15 children with dyslexia versus 15 age-matched and 15 reading-matched controls in a word identification task were examined. The hypothesis underlying the present experiment was that word recognition would be inferior in children with dyslexia, relative to controls, when the task demanded the temporal integration (sequencing) of two-syllable words. Such a hypothesis must predict that one-syllable word recognition does not distinguish between these two populations and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In one study (Shapiro, Ogden, & LindBlad, 1990), this was accomplished by comparing the reading of single words out of context that could be seen in one fixation with words long enough to require two or more fixations. Using words appropriate to the reading level oftheir dyslexic subjects, Shapiro et al (1990) found that dyslexics (who were at least 2 years below grade level in word recognition) performed as well as age-matched controls when reading short words presented for 100 msec or 300 msec, but were worse than controls when reading long words (i.e., words that required a second eye fixation) presented for 300 msec. When the long words were presented for 100 msec, giving insufficient time for a second fixation, dyslexics and controls did not differ.…”
Section: How Dyslexia Might Arise From a Visual Temporal Processing Dmentioning
confidence: 98%
See 1 more Smart Citation
“…In one study (Shapiro, Ogden, & LindBlad, 1990), this was accomplished by comparing the reading of single words out of context that could be seen in one fixation with words long enough to require two or more fixations. Using words appropriate to the reading level oftheir dyslexic subjects, Shapiro et al (1990) found that dyslexics (who were at least 2 years below grade level in word recognition) performed as well as age-matched controls when reading short words presented for 100 msec or 300 msec, but were worse than controls when reading long words (i.e., words that required a second eye fixation) presented for 300 msec. When the long words were presented for 100 msec, giving insufficient time for a second fixation, dyslexics and controls did not differ.…”
Section: How Dyslexia Might Arise From a Visual Temporal Processing Dmentioning
confidence: 98%
“…Both groups were found to make one eye fixation to short words, and two to long words. Shapiro et al (1990) concluded that in dyslexics, information from the second eye fixation was interfering with that from the first. In another study, Hill and Lovegrove (1992) avoided the confound of surrounding print while preserving context by using three conditions to display the same connected discourse: (1) normal text with all the words presented simultaneously; (2) sequential spatial presentation ofthe same words in the same locations as above, but with only one word displayed at a time (this condition requires the same sequence of saccades, but there would be no masking from information in the periphery); and (3) rapid serial visual presentation (RSVP), whereby each word was presented in the same location, using the same time course as in the sequential condition.…”
Section: How Dyslexia Might Arise From a Visual Temporal Processing Dmentioning
confidence: 99%
“…Both types of words were matched on word and syllable length, and multisyllabic words were used to avoid ceiling effects in adult readers. Only words not exceeding nine characters in length were included, because increased word length may increase the chance of saccades when reading within a single word (Shapiro, Ogden, & Lind-Blad, 1990). The mean word length for the two lists of irregular words was 5.37 and 5.23, respectively, whereas those for the two lists of phonologically regular pseudowords were 5.07 and 4.87, respectively.…”
Section: Measure 3: Irregular and Phonologically Regular Pseudoword Rmentioning
confidence: 99%
“…Poor readers, many of whom have poor successive-signal auditory (11)(12)(13)(14)(15)(16)(17) and visual (18) processing, are more vulnerable than good readers to the time compression of sentences (19)(20)(21), although not to speech compression of syllables (22). Comparison of evoked responses suggests that the deficiencies of poor readers at tasks requiring the recognition of time-compressed speech emerge at the cortical level (23).…”
mentioning
confidence: 99%